Champion behaviour and product innovation performance in Korea. Issue 2 (4th May 2018) - Shim, Duksup; Kim, Youngbae
ABSTRACT: Adopting an uncertainty-reduction perspective, this study examines the impact of champion behaviour on the product development process and the performance of new product development projects. Champion behaviour is defined as: expressing confidence in the innovation; involving and motivating others to support the innovation; and persisting under adversity. Based on data from 79 product development projects across 34 Korean firms, this study finds that champion behaviour positively contributes to project performance in both direct and indirect ways by providing market information, material resources, and organisational support. The theoretical and practical implications and directions for future research are discussed.